2022
DOI: 10.3758/s13428-021-01784-2
|View full text |Cite
|
Sign up to set email alerts
|

Testing the validity of a self-report scale, author recognition test, and book counting as measures of lifetime exposure to print fiction

Abstract: We report a study testing the validity of the three most commonly used indicators of lifetime exposure to print fiction, namely a self-report scale, an author recognition test (ART), and book counting, in a sample of older adults (N=306; Mage = 59.29 years, SDage = 7.01). Convergent validity of the self-report scale and book counting was assessed through correlations with the fiction sub-score of the ART; divergent validity of these two indicators was examined via correlations with the non-fiction sub-score of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 141 publications
1
15
0
Order By: Relevance
“…The elaboration of the four dimensions and its categories hopefully might support such decisions and improves the comparison of results between existing studies. In contrast to, for example, reading motivation, where valuable work has already been conducted to provide more clarity regarding the nature of the construct and thus research and its results (e.g., Schiefele et al, 2012;Conradi et al, 2014;Toste et al, 2020), conceptual studies on the reading behavior construct are scarce (e.g., Wimmer and Ferguson, 2022, for an exception). There are hardly any attempts by researchers in the field to examine the terminology of reading behavior in depth, either theoretically and conceptually or at the methodological and operationalization level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elaboration of the four dimensions and its categories hopefully might support such decisions and improves the comparison of results between existing studies. In contrast to, for example, reading motivation, where valuable work has already been conducted to provide more clarity regarding the nature of the construct and thus research and its results (e.g., Schiefele et al, 2012;Conradi et al, 2014;Toste et al, 2020), conceptual studies on the reading behavior construct are scarce (e.g., Wimmer and Ferguson, 2022, for an exception). There are hardly any attempts by researchers in the field to examine the terminology of reading behavior in depth, either theoretically and conceptually or at the methodological and operationalization level.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we want to give an overview of three methods to measure reading behavior that are commonly used in large-scale assessments and surveys in primary and secondary education: questionnaires (global evaluation, differentiated evaluation, and item sets), reading diaries and checklist procedures. Beyond a rather general discussion of these methods, referring to relevant literature dealing with advantages and disadvantages using them (e.g., Fahrenberg et al, 2007 ; Gogol et al, 2014 ; Allen et al, 2022 ; Wimmer and Ferguson, 2022 ), we would like to go into more detail. Therefore, we will share reflections on the specific measurement approaches from example studies in the area of large-scale assessments and surveys, which aim to examine the relation between reading behavior and reading skills in primary and secondary school students (see Table 1 for a summary).…”
Section: Methods That Aim To Measure Reading Behavior Within Large-sc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that both types of scales -self-report measures of reading frequency as well as recognition tests -tend to be satisfying measures of reading behaviour (e.g., Locher & Pfost, 2019;Schroeder et al, 2016). However, the construct overlap seems to be limited (Mol & Bus, 2011;Wimmer & Ferguson, 2022). Therefore, we decided to consider both types of measures as relevant reading behavior outcomes.…”
Section: Instrumentsmentioning
confidence: 99%
“…From a theoretical perspective, the applied reading exposure measure is a more narrow indicator of children's reading of German fiction books, whereas the time spend reading measures grasps all types of reading material, however with an explicit focus on extracurricular reading. From an empirical perspective, prior research has provided evidence that reading exposure checklists and self-report questionnaire items just partially overlap and tend to measure different facets of reading behavior (Spear-Swerling et al, 2010;Wimmer & Ferguson, 2022). Therefore, using both measures jointly tends to better reproduce the reading behavior construct in comparison to the use of just one single measure.…”
Section: Family Literacy Activities Leisure Time Reading and Reading ...mentioning
confidence: 99%